(untitled) (Texas Journal of Medical Science, 2026)
Trauma surgery represents a high-risk area of clinical practice, where timely intervention and preventive strategies are essential to reduce morbidity and mortality. Primary prevention in trauma surgery focuses on implementing risk reduction measures and structured early intervention protocols to minimize the occurrence and severity of traumatic injuries. This article reviews current approaches to risk assessment, injury prevention strategies, and early surgical interventions aimed at improving patient outcomes. Key measures include preoperative risk stratification, adherence to safety protocols, rapid clinical assessment, and prompt initiation of evidence-based interventions.